PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA MIND MAPPING MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN MOTIVASI BELAJAR - Kurniawati, Rindi; Rahman, M Fathur; Sehabuddin, Ahmad (STKIP Persada Khatulistiwa Sintang, 2024)
The implementation of this research was carried out because of the low learning methods used, so that students felt bored in the learning process. The existence of research on the Problem Based Learning learning model with the help of Mind Mapping, namely by forming the experimental class into several small groups using Mind Mapping learning media which makes it easy to do Problem Based Learning learning. This study aims to improve critical thinking skills and learning motivation and conventional learning models. This research is quasi-experimental research with nonequivalent group pretest posttest design. The sample in this study were 72 students. The sampling method used purposive sampling method. Data collection was done by documentation, interviews, observation, and tests. Data analysis techniques by applying paired sample t test and N - Gain test. The results showed that the Problem Based Learning model assisted by Mind Mapping had an effect on improving critical thinking skills and learning motivation of students in class X SMA Negeri 13 Semarang. Based on these findings, the conclusions are: (1) influential to improve critical thinking skills of grade X students, (2) influential to increase student learning motivation Students must be able to play an active role in learning, (3) effectively used to improve critical thinking skills and learning motivation.